2002
DOI: 10.1074/jbc.m106585200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Cellular Response to Oxidative Stress

Abstract: The proteomics analysis reported here shows that a major cellular response to oxidative stress is the modification of several peroxiredoxins. An acidic form of the peroxiredoxins appeared to be systematically increased under oxidative stress conditions. Peroxiredoxins are enzymes catalyzing the destruction of peroxides. In doing so, a reactive cysteine in the peroxiredoxin active site is weakly oxidized (disulfide or sulfenic acid) by the destroyed peroxides. Cellular thiols (e.g. thioredoxin) are used to rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(133 citation statements)
references
References 37 publications
10
122
1
Order By: Relevance
“…Prx I, II, and III (62,63) have all been shown to undergo acidic shifts when cultured cells are subjected to hydroperoxide-mediated oxidative stress. A recent study (64) has demonstrated that the acidic shift of Prx II produced under conditions of oxidative stress was due to conversion of an essential active site cysteine to cysteic acid. The possibility that Prx I undergoes over-oxidation of its cysteine residues due to mutant SOD1 expression FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Prx I, II, and III (62,63) have all been shown to undergo acidic shifts when cultured cells are subjected to hydroperoxide-mediated oxidative stress. A recent study (64) has demonstrated that the acidic shift of Prx II produced under conditions of oxidative stress was due to conversion of an essential active site cysteine to cysteic acid. The possibility that Prx I undergoes over-oxidation of its cysteine residues due to mutant SOD1 expression FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Only the reduced form is prone to overoxidation, whereas the oxidized form is stable. As a consequence, the sulfinic acid form accumulates as a function of turnover number in in vitro assays as well as in cell cultures that could be detected for nonplant 2-Cys Prx by matrix-assisted laser desorption-ionization measurements (40,47). Accumulation during stress treatments (Fig.…”
Section: Inactivation Occurs In Vivo Under Several Stress Conditionsmentioning
confidence: 99%
“…In eukaryotes, 2-Cys Prxs can be temporarily inactivated during catalysis by further reaction of the Cys-SOH with hydroperoxide and formation of a cysteine-sulfinic acid (Cys-SO 2 H) (26,27), and the extent of this inactivation is in proportion with the amount of H 2 O 2 present (28, 29). Cys-SO 2 H in Prx is eventually reduced by the sulfiredoxin Srx1 in S. cerevisiae (22) and mammals (30) and also by mammalian sestrin Hi-95 (31).…”
Section: Tpx1 and Pap1 Interact In Vivomentioning
confidence: 99%